2014
DOI: 10.4103/1305-7456.130591
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial activity of Azadirachta indica, Mimusops elengi, Tinospora cardifolia, Ocimum sanctum and 2% chlorhexidine gluconate on common endodontic pathogens: An in vitro study

Abstract: Objective:To check the antimicrobial activity of Azadirachta indica (Neem), Ocimum sanctum (Tulsi), Mimusops elelngi (Bakul), Tinospora cardifolia (Giloy) and Chlorhexidine Gluconate (CHX) on common endodontic pathogens like Streptococcus mutans, Enterococcus faecalis and staphylococcus aureus.Materials and Methods:The agar diffusion test was used to check the antimicrobial activity of the Methanolic extracts of the medicinal plants along with CHX. Six different concentrations of the tested agents were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 30 publications
2
61
1
Order By: Relevance
“…Similar results were observed by Mistry et al, 26 i.e., < 0.0625% of chlorhexidine against facultative anaerobes but in case of E. faecalis, our study shows higher values though the standard strain of E. faecalis is the same and the MIC also has been determined in both the studies by broth dilution technique. Strict anaerobes, e.g., P. gingivalis as in our study were most susceptible to chlorhexidine without the vehicles, which is contrary to the findings of Filho et al 20 Chlorhexidine when studied with vehicles by agar well diffusion method showed lesser zones of inhibition of P. gingivalis as compared to other microbes due to being more effective against Gram-positive organisms than Gram-negative.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were observed by Mistry et al, 26 i.e., < 0.0625% of chlorhexidine against facultative anaerobes but in case of E. faecalis, our study shows higher values though the standard strain of E. faecalis is the same and the MIC also has been determined in both the studies by broth dilution technique. Strict anaerobes, e.g., P. gingivalis as in our study were most susceptible to chlorhexidine without the vehicles, which is contrary to the findings of Filho et al 20 Chlorhexidine when studied with vehicles by agar well diffusion method showed lesser zones of inhibition of P. gingivalis as compared to other microbes due to being more effective against Gram-positive organisms than Gram-negative.…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that neem has various functional properties, such as killing microbes, being an anti‐inflammatory, preventing cancer, and preventing hypertension . Many studies have found that extract from neem leaves has shown high antioxidant activity because of its active compounds such as phenolic compounds, flavonoids, and limonoids …”
Section: Introductionmentioning
confidence: 99%
“…Neem has documented antimicrobial properties, and can be effective against microbes like Leishmania donovani, against which it also has immunomodulatory action (8). It also has marked acivity against Enterococcus fecalis and S. aureus (9). In our study it was shown that it has anti-E.coli activity and can suppress growth, lecithinase and biofulm formation by the bacterium.…”
Section: Resultsmentioning
confidence: 69%